Method for producing positive electrode active material for non-aqueous electrolyte secondary battery

The method of heat-treating lithium transition metal composite oxides in two stages with controlled particle size distribution addresses inefficiencies in conventional manufacturing, resulting in a positive electrode active material with enhanced durability and output characteristics for non-aqueous electrolyte secondary batteries.

JP7606120B2Active Publication Date: 2024-12-25NICHIA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023097694
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-03-31
Filing Date
2023-06-14
Publication Date
2024-12-25
Estimated Expiration
2037-03-24

AI Technical Summary

Technical Problem

Conventional methods for manufacturing positive electrode active materials for non-aqueous electrolyte secondary batteries are inefficient and complicated, involving multiple steps of grinding and heat-treating lithium-transition metal composite oxides to adjust particle size, leading to potential cracks and reduced durability.

Method used

A method involving the use of lithium transition metal composite oxide particles with a specific composition (Li p Ni x Co y M z O 2+α) that are heat-treated at two stages to achieve a narrow particle size distribution, using a combination of mixing, heat-treating, and dispersion treatments to form single particles or particles with a reduced number of primary particles.

Benefits of technology

This method results in a positive electrode active material with improved durability and output characteristics by minimizing grain boundary dissociation and uniform particle size, enhancing lithium ion diffusion and reducing resistance during charge/discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606120000002
    Figure 0007606120000002
  • Figure 0007606120000003
    Figure 0007606120000003
  • Figure 0007606120000004
    Figure 0007606120000004
Patent Text Reader

Abstract

To provide an efficient manufacturing method for obtaining a cathode active material containing lithium transition metal composite oxide particles consisting of a single particle or reducing the number of primary particles constituting one secondary particle.SOLUTION: The present invention relates to a manufacturing method of a cathode active material including: preparing composite oxide particles, in which a ratio 1D90 / 1D10 of 90% particle diameter 1D90 of cumulative particle size distribution of a volume reference with respect to 10% particle diameter 1D10 is 3 or less, containing nickel; mixing the composite oxide particles with a lithium compound to obtain a first thermally processed product by performing thermal processing respectively at a first temperature and a second temperature higher than the first temperature; and performing dispersion processing of the first thermally processed product. The second temperature is a temperature at which particle growth can be performed while suppressing sintering between particles caused by a residual lithium compound acting as a flux.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery. [Background technology]

[0002] Positive electrode active materials for non-aqueous electrolyte secondary batteries for large power equipment such as electric vehicles are required to have high output characteristics and high durability at the same time. In order to obtain high output characteristics, it is effective to use a positive electrode active material having a structure of secondary particles in which many primary particles are aggregated, to make the inside of the secondary particles hollow to increase the BET, and to reduce the primary particle size of the aggregated secondary particles. However, in such positive electrode active materials, cracks may occur in the secondary particles due to pressure treatment when forming the electrode, expansion and contraction during charging and discharging, etc., and there is room for improvement in durability. In relation to the above-mentioned problems, a positive electrode active material containing lithium transition metal oxide particles in which the number of primary particles constituting a single particle or one secondary particle is reduced, and a method for producing the same have been proposed in which a lithium transition metal composite oxide in which secondary particles are aggregated is pulverized to adjust the particle size of the secondary particles, and the lithium transition metal composite oxide after particle size adjustment is heat-treated again (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-243949 A Summary of the Invention [Problem to be solved by the invention]

[0004] Conventional methods for producing positive electrode active materials are cumbersome and inefficient because they require the lithium transition metal composite oxide, which is an agglomeration of secondary particles obtained by heat treatment, to be pulverized to adjust the particle size, and then the material is subjected to heat treatment again. An object of one embodiment of the present disclosure is to provide an efficient manufacturing method for obtaining a positive electrode active material containing lithium transition metal oxide particles that are composed of a single particle or in which the number of primary particles constituting one secondary particle is reduced. [Means for solving the problem]

[0005] Specific means for solving the above problems are as follows, and the present invention includes the following aspects. 90% particle size of cumulative particle size distribution based on volume 1 D 90 10% particle size 1 D 10 Ratio to 1 D 90 / 1 D 10 a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, the method comprising: preparing composite oxide particles containing nickel; mixing the composite oxide particles and a lithium compound to obtain a first mixture; heat-treating the first mixture at a first temperature and at a second temperature higher than the first temperature to obtain a first heat-treated product; and dispersing the first heat-treated product, the positive electrode active material having an average particle size of 3 or less as determined by observation with an electron microscope. 2 D SEM 50% particle size of cumulative particle size distribution based on volume for 2 D 50 Ratio of 2 D 50 / 2 D SEM is 1 or more and 4 or less, and the lithium transition metal composite oxide particles have a composition represented by the following formula (1): Li p Ni x Co y M 1 z O 2+α (1) In formula (1), p, x, y, z, and α satisfy the following conditions: 1.0≦p≦1.3, 0.3≦x<0.6, 0≦y≦0.4, 0≦z≦0.5, x+y+z=1, and −0.1≦α≦0.1. 1 represents at least one of Mn and Al. Effect of the Invention

[0006] According to one embodiment of the present disclosure, it is possible to provide an efficient production method for obtaining a positive electrode active material containing lithium-lithium transition metal composite oxide particles that are composed of a single particle or in which the number of primary particles constituting one secondary particle is reduced. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a diagram showing an example of an SEM image of the lithium transition metal composite oxide particles according to Example 1. [Diagram 2] FIG. 11 is a diagram showing an example of an SEM image of the lithium transition metal composite oxide particles according to Example 3. [Diagram 3] FIG. 11 is a diagram showing one example of an SEM image of the lithium transition metal composite oxide particles according to Example 4. [Figure 4] FIG. 11 is a diagram showing one example of an SEM image of the lithium transition metal composite oxide particles according to Example 5. [Diagram 5] FIG. 2 is a diagram showing an example of an SEM image of the lithium transition metal composite oxide particles according to Comparative Example 1. [Figure 6] FIG. 13 is a diagram showing an example of an SEM image of the lithium transition metal composite oxide particles according to Comparative Example 2. [Figure 7] FIG. 11 is a diagram showing one example of an SEM image of the lithium transition metal composite oxide particles according to Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, the manufacturing method of the positive electrode active material for non-aqueous electrolyte secondary batteries according to the present disclosure will be described based on the embodiments. However, the embodiments shown below are intended to embody the technical idea of ​​the present invention, and do not limit the present invention to the following. In this specification, the content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified.

[0009] [Method of manufacturing positive electrode active material for non-aqueous electrolyte secondary battery] In one embodiment of the present disclosure, a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery is provided. 1 D 90 10% particle size 1 D 10 Ratio to 1 D 90 / 1 D 10 The method includes preparing composite oxide particles (hereinafter also referred to as "first composite oxide particles") containing nickel, mixing the first composite oxide particles and a lithium compound to obtain a first mixture, heat-treating the first mixture at a first temperature and a second temperature higher than the first temperature to obtain a first heat-treated product, and dispersing the first heat-treated product. The obtained positive electrode active material has an average particle size of 1.0 μm or less based on observation with an electron microscope. 2 D SEM 50% particle size of cumulative particle size distribution based on volume for 2 D 50 Ratio of 2 D 50 / 2 D SEM is 1 or more and 4 or less, and the lithium transition metal composite oxide particles have a composition represented by the following formula (1): Li p Ni x Co y M 1 z O 2+α (1) In formula (1), p, x, y, z, and α satisfy the following conditions: 1.0≦p≦1.3, 0.3≦x<0.6, 0≦y≦0.4, 0≦z≦0.5, x+y+z=1, and −0.1≦α≦0.1. 1 represents at least one of Mn and Al.

[0010] 1 D 90 / 1 D 10Using first composite oxide particles having a uniform particle size of 3 or less as a raw material, this is heat-treated together with a lithium compound, and then a dispersion treatment is carried out instead of a pulverization treatment, thereby efficiently producing lithium transition metal composite oxide particles that are particles consisting of a single particle or particles composed of a few primary particles (hereinafter, also simply referred to as "single particles"). In a conventional method for producing a positive electrode active material consisting of a single particle, the particle size is adjusted by pulverization, but it is difficult to control the particle size distribution, and it is particularly difficult to obtain a sharp particle size distribution with uniform particle size.

[0011] The first composite oxide particles used in the method for producing a positive electrode active material contain at least nickel, and preferably contain nickel and at least one element selected from the group consisting of cobalt, manganese and aluminum, and more preferably contain nickel, cobalt, and at least one of manganese and aluminum.

[0012] The first composite oxide particles are 1 D 90 / 1 D 10 is 3 or less, and preferably 2 or less. The first composite oxide particles have a 50% particle size of the cumulative particle size distribution based on volume. 1 D 50 is, for example, 12 μm or less, preferably 6 μm or less, more preferably 4 μm or less, and is, for example, 1 μm or more, preferably 2 μm or more.

[0013] When the first composite oxide particles contain nickel, cobalt, and at least one of manganese and aluminum, the content ratio of nickel, cobalt, manganese, and aluminum, Ni / Co / (Mn+Al), can be, for example, 1 / 1 / 1, 1 / 1 / (0.5 / 0.5), etc. on a molar basis.

[0014] The first composite oxide particles may be prepared by appropriately selecting from commercially available products, or may be prepared by manufacturing a product having desired properties. When manufacturing the first composite oxide particles, for example, the first composite oxide particles can be manufactured by heat treating a composite hydroxide containing a desired metal element. The composite hydroxide can be obtained by, for example, a coprecipitation method in which a raw material compound soluble in a solvent is dissolved, and a composite hydroxide with a desired composition is obtained by adjusting the temperature, adjusting the pH, adding a complexing agent, etc. For details of the method of obtaining a composite oxide by the coprecipitation method, JP 2003-292322 A, JP 2011-116580 A, etc. can be referred to.

[0015] The first composite oxide particles thus prepared are mixed with a lithium compound to prepare a first mixture. Examples of the lithium compound include lithium hydroxide, lithium carbonate, and lithium oxide.

[0016] The particle size of the lithium compound used is, for example, 0.1 μm or more and 100 μm or less, and preferably 2 μm or more and 20 μm or less, as the 50% particle size of the cumulative particle size distribution on a volume basis. The ratio of the total number of moles of lithium to the total number of moles of metal elements constituting the first composite oxide particles in the first mixture is, for example, 1 or more and 1.3 or less, and more preferably 1 or more and 1.25 or less.

[0017] The first composite oxide particles and the lithium compound can be mixed using, for example, a high-speed shear mixer.

[0018] The resulting first mixture is subjected to a first heat treatment at a first temperature, and then a second heat treatment at a second temperature higher than the first temperature to obtain a first heat-treated product. By performing heat treatment in two stages, a first heat treatment at a relatively low temperature and a second heat treatment at a relatively high temperature, for example, the reaction between the lithium compound and the first composite oxide is sufficiently carried out in the first heat treatment to reduce the residual lithium compound in a temperature range where single particle formation does not occur, and in the second heat treatment, particle growth can be carried out while suppressing sintering between particles caused by the residual lithium compound acting as a flux.

[0019] The heat treatment of the first mixture is, for example, performed by raising the temperature from room temperature to a first temperature, performing heat treatment at the first temperature for a predetermined time, then raising the temperature to a second temperature, performing heat treatment at the second temperature for a predetermined time, and then lowering the temperature to, for example, room temperature, thereby obtaining a first heat-treated product. The first heat-treated product may be heat-treated at at least two temperatures, and may further be subjected to an additional heat treatment at a temperature higher than the second temperature after the second heat treatment.

[0020] The first temperature is, for example, 850° C. or more and 950° C. or less, and preferably 900° C. or more and 940° C. or less. The second temperature is, for example, 980° C. or more and 1100° C. or less, and preferably 1000° C. or more and 1080° C. or less. The difference between the first temperature and the second temperature is, for example, 30° C. or more, preferably 100° C. or more, and, for example, 250° C. or less, preferably 180° C. or less.

[0021] The heat treatment time of the first heat treatment is, for example, from 1 hour to 20 hours, and preferably from 5 hours to 10 hours. The heat treatment time of the second heat treatment is, for example, from 1 hour to 20 hours, and preferably from 5 hours to 10 hours. The heat treatment time of the first heat treatment and the heat treatment time of the second heat treatment may be the same or different. When they are different, for example, the heat treatment time of the second heat treatment can be longer than the heat treatment time of the first heat treatment. Specifically, for example, the heat treatment time of the second heat treatment can be 1.05 to 2 times the heat treatment time of the first heat treatment, and preferably 1.1 to 1.5 times. Here, the first heat treatment and the second heat treatment may be performed continuously or independently. When the first heat treatment and the second heat treatment are performed continuously, the temperature rise rate from the first temperature to the second temperature can be, for example, 5° C. / min.

[0022] The heat treatment may be performed in air or in an oxygen atmosphere. The heat treatment can be carried out using, for example, a box furnace, a rotary kiln furnace, a pusher furnace, a roller hearth kiln furnace, or the like.

[0023] The first heat-treated product is subjected to a dispersion treatment. The dispersion treatment is not a pulverization treatment involving strong shearing forces or impacts, but rather involves dissociation of the sintered primary particles, thereby obtaining lithium transition metal composite oxide particles with a narrow particle size distribution and uniform particle size. The dispersion treatment may be performed in a dry or wet manner, with a dry method being preferred. The dispersion treatment may be performed using, for example, a ball mill, a jet mill, or the like. The conditions for the dispersion treatment are, for example, the amount of the lithium transition metal composite oxide particles after the dispersion treatment. 2 D 50 / 2 D SEM can be set to be in a desired range, for example, 1 or more and 4 or less.

[0024] For example, when the dispersion treatment is performed using a ball mill, a resin media can be used. Examples of the resin media include urethane resin and nylon resin. Generally, alumina, zirconia, and the like are used as media materials for ball mills, and particles are pulverized by these media. In contrast, by using resin media, the particles are not pulverized, and the sintered primary particles are dissociated. The size of the resin media can be, for example, φ5 mm to 30 mm. Also, for the body (shell), for example, urethane resin, nylon resin, and the like can be used. The dispersion treatment time is, for example, 3 to 60 minutes, and preferably 10 to 30 minutes. The conditions for the dispersion treatment using a ball mill are as follows: 2 D 50 / 2 D SEM The first composite oxide particles as the raw material are 1 D 90 / 1 D 10 Depending on the above, the amount of media, rotation or oscillation speed, dispersion time, media specific gravity, etc. may be adjusted.

[0025] For example, when the dispersion process is carried out using a jet mill, the primary particles are not pulverized, and the desired 2 D 50 / 2 D SEM The first composite oxide particles as the raw material are1 D 90 / 1 D 10 The supply pressure, grinding pressure, supply speed, etc. may be adjusted according to the above. The supply pressure may be, for example, 0.1 to 0.5 MPa, and the grinding pressure may be, for example, 0.1 to 0.6 MPa. According to the above-described manufacturing method, a positive electrode active material containing single-particle lithium transition metal composite oxide particles can be efficiently manufactured.

[0026] One embodiment of the manufacturing method may further include mixing the first heat-treated product after the dispersion treatment with a lithium compound to obtain a second mixture, and heat-treating the resulting second mixture to obtain a second heat-treated product. By adding the lithium compound in multiple batches to obtain mixtures and heat-treating each mixture, lithium transition metal composite oxide particles with a narrower particle size distribution and more uniform particle size tend to be obtained. The first heat-treated product includes, for example, a lithium transition metal composite oxide.

[0027] The lithium compound in the second mixture is as described above in detail. The lithium compound in the second mixture may be used alone or in combination of two or more kinds, and may be the same as or different from the lithium compound in the first mixture.

[0028] The ratio of the total number of moles of lithium to the total number of moles of metal elements other than lithium constituting the first heat-treated product in the second mixture is, for example, from 1.0 to 1.3, and preferably from 1.08 to 1.22. When the lithium compound is added in multiple portions, the ratio of the total number of moles of lithium to the total number of moles of metal elements contained in the first composite oxide in the first mixture is, for example, from 0.75 to 1.27, and preferably from 0.9 to 1.07.

[0029] The first heat-treated product and the lithium compound can be mixed using, for example, a high-speed shear mixer.

[0030] The obtained second mixture is heat-treated to obtain a second heat-treated product containing lithium transition metal composite oxide particles. The temperature of the heat treatment is, for example, 650° C. or higher, preferably 800° C. or higher, and, for example, 970° C. or lower, preferably 950° C. or lower. The heat treatment may be performed at a single temperature or at multiple temperatures.

[0031] The heat treatment time of the second mixture is, for example, from 1 hour to 20 hours, and preferably from 5 hours to 15 hours. The heat treatment atmosphere of the second mixture may be air or an oxygen atmosphere.

[0032] The second heat-treated product after the heat treatment may be subjected to a dispersion treatment as necessary, the details of which are as described above. The lithium transition metal composite oxide particles obtained by subjecting the second mixture to the heat treatment and dispersion treatment have a narrower particle size distribution, and serve as a positive electrode active material having superior output characteristics and durability.

[0033] The lithium transition metal composite oxide particles obtained by the above-mentioned production method have a composition represented by formula (1) and an average particle diameter based on observation with an electron microscope. 2 D SEM 50% particle size in cumulative particle size distribution based on volume 2 D 50 Ratio of 2 D 50 / 2 D SEM The particle size distribution is 1 or more and 4 or less. 2 D 90 10% particle size 2 D 10 Ratio to 2 D 90 / 2 D 10 It is preferable that the ratio is 4 or less.

[0034] 2 D 50 / 2 D SEMThe fact that the value is 1 or more and 4 or less means that the lithium transition metal composite oxide particle is a single particle or is composed of a small number of primary particles, and there are few contact grain boundaries between the primary particles. 2 D 90 / 2 D 10 A value of 4 or less means that the distribution width in the cumulative particle size distribution based on the volume of the lithium transition metal composite oxide particles is narrow and the particle sizes are uniform. A positive electrode active material containing lithium transition metal composite oxide particles with such characteristics is expected to achieve both excellent output characteristics and excellent durability.

[0035] Compared to positive electrode active materials containing conventional single-particle lithium transition metal composite oxide particles with secondary particles consisting of a large number of aggregated primary particles, positive electrode active materials containing single-particle lithium transition metal composite oxide particles exhibit excellent durability because they suppress the decrease in capacity retention rate due to the disconnection of the lithium ion conductive path caused by grain boundary dissociation of the secondary particles during charge / discharge cycles, and the increase in the diffusion movement resistance of lithium ions. On the other hand, a three-dimensional grain boundary network like that of positive electrode active materials made of aggregated particles is hardly formed, making it impossible to design a high output that utilizes grain boundary conduction, and so the output characteristics tend to be insufficient. In order to improve the output characteristics, the particle size of the single particles ( 2 D SEM However, if the particle size is too small, the interactions between the powder particles increase, which tends to significantly worsen the plate packing, and the powder flowability decreases, which can significantly worsen handling. On the other hand, a certain particle size is necessary to obtain a practical energy density, but if the particle size is large, it is thought that the output deficiency tends to become more pronounced.

[0036] The lithium transition metal composite oxide particles of one embodiment according to the present disclosure have a more uniform particle size than conventional single particles. Therefore, even when charging and discharging are performed at a high current density, unevenness in the charge and discharge depth for each particle due to current concentration in some particles can be suppressed. It is therefore considered that local deterioration due to cycling can be suppressed while suppressing an increase in resistance due to current concentration.

[0037] Furthermore, because the particle size of the lithium transition metal composite oxide particles is uniform, the particles do not collapse even when pressed under high pressure when preparing an electrode, and it is believed that the gaps between the particles can be made uniform. When a battery is constructed, the gaps between the particles are filled with electrolyte to become a diffusion path for lithium ions, and it is believed that the uniform size of the diffusion path can suppress unevenness in charging and discharging for each particle. As a result, it is believed that even lithium transition metal composite oxide particles with few contact grain boundaries between primary particles can achieve excellent output characteristics while ensuring plate filling properties.

[0038] In addition, when synthesizing single particles, a high heat treatment temperature is generally required to grow the particles. In particular, in compositions with a high Ni ratio, high-temperature sintering may cause Ni elements to be mixed into the Li site, i.e., disorder. Disorder is preferable to suppress because it inhibits the diffusion of Li ions in the lithium transition metal composite oxide particles, becomes resistance, and has effects such as a decrease in charge / discharge capacity at practical current density and a decrease in output characteristics. By suppressing disorder, it is possible to achieve better capacity and output characteristics in single particles.

[0039] The lithium transition metal composite oxide particles that make up the positive electrode active material have an average particle size based on electron microscope observation. 2 D SEM From the viewpoints of output characteristics and electrode plate packing property, it is preferably 1.5 μm or more, more preferably 5.5 μm or less, and more preferably 3 μm or less.

[0040] Average particle size based on electron microscope observation 2 D SEM is obtained by observing using a scanning electron microscope (SEM) at magnifications of 1,000 to 10,000 times depending on the particle size, selecting 100 particles whose particle outlines can be confirmed, calculating the equivalent sphere diameter of the selected particles using image processing software, and then taking the arithmetic mean of the obtained equivalent sphere diameters.

[0041] The lithium transition metal composite oxide particles are 50% particle size in the cumulative particle size distribution based on volume. 2 D 50 Average particle size based on electron microscope observation 2 D SEM The ratio to 2 D 50 / 2 D SEM When the value is 1, it indicates a single particle, and the closer it is to 1, the fewer the number of primary particles it contains. 2 D 50 / 2 D SEM From the standpoint of durability, 2 D 50 / 2 D SEM is preferably 1 or more and 4 or less, and from the viewpoint of output characteristics, is preferably 3 or less, and particularly preferably 2.5 or less.

[0042] In addition, the 50% particle size of the lithium transition metal composite oxide particles 2 D 50 is, for example, 1 μm or more, preferably 1.5 μm or more, and is, for example, 21 μm or less, preferably 5.5 μm or less, and more preferably 3 μm or less.

[0043] 50% particle size 2 D 50 is calculated as the particle size corresponding to the cumulative 50% from the small diameter side in the cumulative particle size distribution on a volume basis measured under wet conditions using a laser diffraction particle size distribution analyzer. Similarly, the 90% particle size 2 D 90 and 10% particle size 2 D 10 are calculated as the particle diameters corresponding to the cumulative 90% and 10% from the small diameter side, respectively.

[0044] The lithium transition metal composite oxide particles are 90% particle size in the cumulative particle size distribution based on volume. 2 D 90 10% particle size 2 D 10 Ratio to 2 D 90 / 2 D 10From the viewpoint of output characteristics, it is preferably 4 or less, more preferably 3 or less, and still more preferably 2.5 or less.

[0045] The lithium transition metal composite oxide constituting the lithium transition metal composite oxide particles has a composition represented by the above formula (1). Further, the lithium transition metal composite oxide preferably has a layered structure. Examples of the lithium transition metal composite oxide having the composition represented by the formula (1) and having a layered structure include lithium nickel composite oxide, lithium nickel cobalt manganese composite oxide, and the like.

[0046] In the formula (1), from the viewpoint of output characteristics, p preferably satisfies 1.1 ≦ p ≦ 1.2. From the viewpoint of productivity, x preferably satisfies 0.3 ≦ x < 0.5. From the viewpoint of material cost, y preferably satisfies 0 < y ≦ 0.33, and from the viewpoint of charge-discharge capacity and output characteristics, z preferably satisfies 0 < z ≦ 0.4. Also, x:z is preferably from 3:1 to 1:1, and more preferably from 2:1 to 1:1.

[0047] The positive electrode active material may be doped with an element other than the elements constituting the lithium transition metal composite oxide in the lithium transition metal composite oxide particles obtained by the above production method. Examples of the element to be doped include B, Na, Mg, Si, P, S, K, Ca, Ti, V, Cr, Zn, Sr, Y, Zr, Nb, Mo, In, Sn, Ba, La, Ce, Nd, Sm, Eu, Gd, Ta, W, and Bi. Examples of the compound used for doping these elements include oxides, fluorides, and Li composite oxides containing these elements. The doping amount can be, for example, 0.005 mol% or more and 10 mol% or less with respect to the lithium transition metal composite oxide particles.

[0048] The positive electrode active material may have a core particle containing a lithium transition metal composite oxide obtained by the above-mentioned manufacturing method, and an attachment disposed on the surface of the core particle. The attachment may be disposed on at least a part of the surface area of ​​the core particle, and is preferably disposed on an area of ​​1% or more of the surface area of ​​the core particle. The composition of the attachment is appropriately selected depending on the purpose, and examples thereof include oxides and fluorides containing at least one selected from the group consisting of B, Na, Mg, Si, P, S, K, Ca, Ti, V, Cr, Zn, Sr, Y, Zr, Nb, Mo, In, Sn, Ba, La, Ce, Nd, Sm, Eu, Gd, Ta, W, and Bi, and Li composite oxides thereof. The content of the attachment may be, for example, 0.03% by mass or more and 10% by mass or less in the lithium transition metal composite oxide particles, and preferably 0.1% by mass or more and 2% by mass or less.

[0049] From the viewpoint of the initial efficiency of the non-aqueous electrolyte secondary battery, the lithium transition metal composite oxide preferably has a disorder of nickel element determined by X-ray diffraction method of 4.0% or less, more preferably 2.0% or less, and even more preferably 1.5% or less. Here, the disorder of nickel element means a chemical disorder of the transition metal ion (nickel ion) that should occupy the original site. In the lithium transition metal composite oxide with a layered structure, the representative example is the replacement of the lithium ion that should occupy the site represented by 3b (3b site, the same below) and the transition metal ion that should occupy the 3a site when expressed by the Wyckoff symbol. The smaller the disorder of nickel element, the more preferable it is because the initial efficiency is improved.

[0050] The positive electrode active material produced by the manufacturing method of one embodiment of the present disclosure can be used in the positive electrode of a nonaqueous electrolyte secondary battery to constitute a nonaqueous electrolyte secondary battery that can achieve both excellent output characteristics and excellent durability. The positive electrode active material can be included in a positive electrode active material layer disposed on a current collector to constitute a positive electrode. That is, the present invention encompasses an electrode for a nonaqueous electrolyte secondary battery that includes the positive electrode active material produced by the manufacturing method, and a nonaqueous electrolyte secondary battery that includes the electrode.

[0051] [Nonaqueous electrolyte secondary battery electrode] The electrode for a non-aqueous electrolyte secondary battery includes a current collector and a positive electrode active material layer disposed on the current collector and containing the positive electrode active material for a non-aqueous electrolyte secondary battery produced by the above-mentioned production method. A non-aqueous electrolyte secondary battery including such an electrode can achieve high durability and high output characteristics.

[0052] Examples of the material of the current collector include aluminum, nickel, stainless steel, etc. The positive electrode active material layer can be formed by applying a positive electrode mixture obtained by mixing the above-mentioned positive electrode active material, conductive material, binder, etc. with a solvent onto the current collector, and then performing a drying process, a pressure process, etc. Examples of the conductive material include natural graphite, artificial graphite, acetylene black, etc. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyamide acrylic resin, etc.

[0053] [Non-aqueous electrolyte secondary battery] The non-aqueous electrolyte secondary battery comprises the above-mentioned electrode for non-aqueous electrolyte secondary battery. The non-aqueous electrolyte secondary battery comprises, in addition to the electrode for non-aqueous electrolyte secondary battery, a negative electrode for non-aqueous secondary battery, a non-aqueous electrolyte, a separator, etc. In the non-aqueous electrolyte secondary battery, the negative electrode, non-aqueous electrolyte, separator, etc., for example, those for non-aqueous electrolyte secondary batteries described in JP 2002-075367 A, JP 2011-146390 A, JP 2006-12433 A (the entire disclosures of which are incorporated herein by reference) can be appropriately used. EXAMPLES

[0054] Hereinafter, examples of the present invention will be described in detail.

[0055] First, the methods for measuring physical properties in the following Examples and Comparative Examples will be described. 1 D 10 and 2 D 10 , 1 D50 and 2 D 50 ,and 1 D 90 and 2 D 90 For the above, a laser diffraction particle size distribution analyzer (SALD-3100, manufactured by Shimadzu Corporation) was used to measure the cumulative particle size distribution on a volume basis, and the particle sizes were calculated corresponding to the cumulative size from the smallest diameter side. Average particle size based on electron microscope observation 1 D SEM and 2 D SEM In the study, 100 particles whose particle outlines could be confirmed were selected from images observed at 1,000 to 10,000 times magnification using a scanning electron microscope (SEM), and the spherical equivalent diameter of the selected particles was calculated using image processing software (ImageJ), and the arithmetic mean value of the obtained spherical equivalent diameters was obtained.

[0056] The disorder value of nickel element (Ni disorder amount) was determined by X-ray diffraction method according to the following procedure. The obtained lithium transition metal composite oxide particles were subjected to X-ray diffraction spectrum measurement using CuKα radiation (tube current 200 mA, tube voltage 45 kV). Based on the obtained X-ray diffraction spectrum, a composition model was created based on Li 1-d Ni d The lithium transition metal composite oxide was subjected to structural optimization by Rietveld analysis using Rietan2000 software, with MeO2 (Me being the transition metal other than nickel in the lithium transition metal composite oxide). The percentage of d calculated as a result of structural optimization was taken as the amount of Ni disorder.

[0057] Example 1 (Seed generation process) First, 10 kg of water was placed in the reaction tank and the ammonium ion concentration was adjusted to 1.8% by mass while stirring. The temperature inside the tank was set to 25°C, nitrogen gas was circulated, and the oxygen concentration in the space inside the reaction tank was maintained at 10% or less. A 25% by mass aqueous solution of sodium hydroxide was added to the water in the reaction tank to adjust the pH value of the solution in the tank to 13.5 or more. Next, a mixed aqueous solution of nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 1:1:1 was prepared. The mixed aqueous solution was added until the solute amount became 4 moles, and seeds were generated while controlling the pH value of the reaction solution to 12.0 or more with a sodium hydroxide solution.

[0058] (Crystallization process) After the seed generation step, the temperature in the tank was maintained at 25°C or higher until the end of the crystallization step. A mixed aqueous solution of 1200 moles of solute was prepared and, together with the aqueous ammonia solution, was simultaneously added over a period of 5 hours or more to the reaction tank while maintaining the ammonium ion concentration in the solution at 2000 ppm or higher so as to prevent new seed generation. During the reaction, the pH value in the reaction solution was controlled to be maintained at 10.5 to 12.0 with a sodium hydroxide solution. Sampling was carried out successively during the reaction, and the D of the composite hydroxide particles was measured. 50 The addition was stopped when the particle size reached approximately 4.5 μm. The product was then washed with water, filtered, and dried to obtain composite hydroxide particles. The obtained hydroxide precursor was heat-treated at 300°C for 20 hours in an air atmosphere to obtain a composite hydroxide particle having a composition ratio of Ni / Co / Mn=0.33 / 0.33 / 0.33. 1 D 10 = 3.4 μm, 1 D 50 = 4.5 μm, 1 D 90 = 6.0 μm, 1 D 90 / 1 D 10 = 1.8.

[0059] (synthesis process) The first composite oxide particles obtained and lithium carbonate were mixed so that Li / (Ni+Co+Mn)=1.15 to obtain a raw material mixture. The raw material mixture obtained was fired in air at 925°C for 7.5 hours, and then fired at 1030°C for 6 hours to obtain a sintered body. The sintered body obtained was crushed, and a dispersion treatment was performed once using a jet mill with a supply pressure of 0.2 MPa and a crushing pressure of 0.1 MPa adjusted so that the primary particles were not crushed, and the mixture was sieved through a dry sieve to obtain a powdered body. From the above, the average particle size based on the electron microscope observation2 D SEM is 2.8 μm, 2 D 10 = 2.9 μm, 2 D 50 = 5.0 μm, 2 D 90 =7.9μm, average particle size 2 D SEM for 2 D 50 Ratio of 2 D 50 / 2 D SEM is 1.8, and the ratio in particle size distribution 2 D 90 / 2 D 10 is 2.7, the Ni disorder amount is 0.6%, and the composition formula is Li 1.15 Ni 0.33 Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles represented by O2 were obtained. The physical properties of the obtained lithium transition metal composite oxide particles are shown in Table 1, and an SEM image is shown in Figure 1.

[0060] Example 2 The timing of finishing the addition of the mixed aqueous solution in the crystallization process in Example 1 was determined based on the D 50 The same conditions were used except that the thickness was changed when the thickness reached about 3.0 μm. The composition ratio of Ni / Co / Mn was 0.33 / 0.33 / 0.33. 1 D 10 = 2.2 μm, 1 D 50 = 3.0 μm, 1 D 90 = 4.1 μm, 1 D 90 / 1 D 10=1.9. The first composite oxide particles obtained were mixed with lithium carbonate so that Li / (Ni+Co+Mn)=1.05 to obtain a raw material mixture. The raw material mixture obtained was fired in air at 925°C for 7.5 hours, and then fired at 1030°C for 6 hours to obtain a sintered body. The sintered body obtained was crushed, dispersed in a resin ball mill for 30 minutes, and sieved in a dry sieve to obtain a powdered body. The powdered body obtained was mixed with lithium carbonate so that Li / (Ni+Co+Mn)=1.17, and sieved in air at 700°C for 10 hours to obtain a sintered body. The sintered body obtained was crushed, dispersed in a resin ball mill for 30 minutes, and sieved in a dry sieve to obtain a powdered body. From the above, the average particle size 2 D SEM is 1.2 μm, 2 D 10 = 1.4 μm, 2 D 50 = 3.2 μm, 2 D 90 =5.1μm, average particle size 2 D SEM for 2 D 50 Ratio of 2 D 50 / 2 D SEM is 2.7, and the ratio in particle size distribution 2 D 90 / 2 D 10 is 3.6, Ni disorder amount is 1.7%, and the composition formula is Li 1.17 Ni 0.33 Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles represented by O2 were obtained. The physical properties of the obtained lithium transition metal composite oxide particles are shown in Table 1.

[0061] Example 3 The first composite oxide particles were obtained under the same conditions as in Example 2. The obtained first composite oxide particles and lithium carbonate were mixed so that Li / (Ni+Co+Mn)=1.05 to obtain a raw material mixture. The obtained raw material mixture was fired in air at 925°C for 7.5 hours, and then fired at 1030°C for 6 hours to obtain a sintered body. The obtained sintered body was crushed, subjected to a dispersion treatment in a resin ball mill for 30 minutes, and sieved to obtain a powdered body. The obtained powdered body and lithium carbonate were mixed so that Li / (Ni+Co+Mn)=1.17, and sieved in air at 900°C for 10 hours to obtain a sintered body. The obtained sintered body was crushed, subjected to a dispersion treatment in a resin ball mill for 30 minutes, and sieved to obtain a powdered body. From the above, the average particle size 2 D SEM is 1.2 μm, 2 D 10 = 1.5 μm, 2 D 50 = 3.3 μm, 2 D 90 =5.1μm, average particle size 2 D SEM for 2 D 50 Ratio of 2 D 50 / 2 D SEM is 2.8, and the particle size distribution 2 D 90 / 2 D 10 The ratio is 3.4, the Ni disorder amount is 0.9%, and the composition formula is Li 1.17 Ni 0.33 Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles represented by O2 were obtained. The physical properties of the obtained lithium transition metal composite oxide particles are shown in Table 1, and an SEM image is shown in Figure 2.

[0062] Example 4 The first composite oxide particles were obtained under the same conditions as in Example 2. The obtained first composite oxide particles and lithium carbonate were mixed so that Li / (Ni+Co+Mn)=1.05 to obtain a raw material mixture. The obtained raw material mixture was fired in air at 925°C for 7.5 hours, and then fired at 1030°C for 6 hours to obtain a sintered body. The obtained sintered body was crushed, dispersed in a resin ball mill for 30 minutes, and sieved to obtain a powder. The obtained powder and lithium carbonate were mixed so that Li / (Ni+Co+Mn)=1.17, and sieved in air at 900°C for 10 hours to obtain a sintered body. The obtained sintered body was crushed, and the supply pressure was adjusted to 0.4 MPa and the crushing pressure was 0.55 MPa using a jet mill so that the primary particles were not crushed, and the dispersion treatment was performed twice, followed by sieving to obtain a powder. From the above, the average particle size 2 D SEM is 1.4 μm, 2 D 10 = 1.1 μm, 2 D 50 = 1.9 μm, 2 D 90 =2.8μm, average particle size 2 D SEM for 2 D 50 Ratio of 2 D 50 / 2 D SEM is 1.4, and the particle size distribution 2 D 90 / 2 D 10 The ratio is 2.5, the amount of Ni disorder is 1.0%, and the composition formula is Li 1.17 Ni 0.33 Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles represented by O2 were obtained. The physical properties of the obtained lithium transition metal composite oxide particles are shown in Table 1, and an SEM image is shown in Figure 3.

[0063] Example 5 The timing of finishing the addition of the mixed aqueous solution in the crystallization process in Example 1 was determined based on the D 50The same conditions were used except that the thickness was changed when the thickness reached 9.9 μm. The composition ratio of Ni / Co / Mn was 0.33 / 0.33 / 0.33. 1 D 10 = 8.6 μm, 1 D 50 = 9.9 μm, 1 D 90 = 12.7 μm, 1 D 90 / 1 D 10 = 1.5. The obtained first composite oxide particles and lithium carbonate were mixed so that Li / (Ni+Co+Mn) = 1.05 to obtain a raw material mixture. The obtained raw material mixture was fired in air at 925°C for 7.5 hours, and then fired at 1080°C for 6 hours to obtain a sintered body. The obtained sintered body was crushed, dispersed in a resin ball mill for 10 minutes, and sieved in a dry sieve to obtain a powdered body. The obtained powdered body and lithium carbonate were mixed so that Li / (Ni+Co+Mn) = 1.14, and sieved in air at 900°C for 10 hours to obtain a sintered body. The obtained sintered body was crushed, dispersed in a resin ball mill for 10 minutes, and sieved in air at 900°C to obtain a powdered body. From the above, the average particle size 2 D SEM is 6.8 μm, 2 D 10 = 7.6 μm, 2 D 50 = 10.4 μm, 2 D 90 =16.4μm, average particle size 2 D SEM for 2 D 50 Ratio of 2 D 50 / 2 D SEM is 1.5, and in the particle size distribution 2 D 90 / 2 D 10 The ratio is 2.2, the Ni disorder amount is 1.1%, and the composition formula is Li 1.14 Ni 0.33 Co 0.33 Mn 0.33The lithium transition metal composite oxide particles represented by O2 were obtained. The physical properties of the obtained lithium transition metal composite oxide particles are shown in Table 1, and an SEM image is shown in Figure 4.

[0064] Example 6 The first composite oxide particles were obtained under the same conditions as in Example 2. The obtained first composite oxide particles and lithium carbonate were mixed so that Li / (Ni+Co+Mn)=1.05 to obtain a raw material mixture. The obtained raw material mixture was fired in air at 925°C for 7.5 hours, and then fired at 1030°C for 6 hours to obtain a sintered body. The obtained sintered body was crushed, subjected to a dispersion treatment in a resin ball mill for 10 minutes, and sieved in a dry sieve to obtain a powdered body. The obtained powdered body and lithium carbonate were mixed so that Li / (Ni+Co+Mn)=1.14, and sieved in air at 900°C for 10 hours to obtain a sintered body. The obtained sintered body was crushed, subjected to a dispersion treatment in a resin ball mill for 10 minutes, and sieved in a dry sieve to obtain a powdered body. From the above, the average particle size 2 D SEM is 1.25 μm, 2 D 10 = 2.7 μm, 2 D 50 = 4.5 μm, 2 D 90 = 6.7μm, average particle size of primary particles 2 D SEM for 2 D 50 Ratio of 2 D 50 / 2 D SEM is 3.6, and the particle size distribution 2 D 90 / 2 D 10 The ratio is 2.5, the amount of Ni disorder is 1.0%, and the composition formula is Li 1.14 Ni 0.33 Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles represented by O2 were obtained. The physical properties of the obtained lithium transition metal composite oxide particles are shown in Table 1, and an SEM image is shown in Figure 5.

[0065] Comparative Example 1 During the crystallization reaction in Example 1, the seed slurry prepared in the seed generation process was separately added to the reaction tank several times, and the timing for finishing the addition of the mixed aqueous solution was adjusted to the D of the composite hydroxide particles. 50 The same conditions were used except that the thickness was changed when the thickness reached 5.0 μm. The composition ratio of Ni / Co / Mn was 0.33 / 0.33 / 0.33. 1 D 10 = 2.4 μm, 1 D 50 = 5.0 μm, 1 D 90 = 12.2 μm, 1 D 90 / 1 D 10 = 5.1. The obtained composite oxide particles and lithium carbonate were mixed so that Li / (Ni+Co+Mn) = 1.05 to obtain a raw material mixture. The obtained raw material mixture was fired in air at 925°C for 7.5 hours, and then fired at 1030°C for 6 hours to obtain a sintered body. The obtained sintered body was crushed, dispersed in a resin ball mill for 10 minutes, and sieved in a dry sieve to obtain a powdered body. The obtained powdered body and lithium carbonate were mixed so that Li / (Ni+Co+Mn) = 1.14, and sieved in air at 900°C for 10 hours to obtain a sintered body. The obtained sintered body was crushed, dispersed in a resin ball mill for 10 minutes, and sieved in air for 10 hours to obtain a powdered body. From the above, the average particle size 2 D SEM is 3.65 μm, 2 D 10 = 2.5 μm, 2 D 50 = 7.0 μm, 2 D 90 = 13.5 μm, for the average particle size of the primary particles 2 D 50 Ratio of 2 D 50 / 2 D SEM is 1.9, and the particle size distribution 2 D 90 / 2 D 10 The ratio is 5.4, the Ni disorder amount is 0.9%, and the composition formula is Li 1.14 Ni 0.33 Co 0.33Mn 0.33 The lithium transition metal composite oxide particles represented by O2 were obtained. The physical properties of the obtained lithium transition metal composite oxide particles are shown in Table 1, and an SEM image is shown in Figure 6.

[0066] Comparative Example 2 First composite oxide particles were obtained under the same conditions as in Example 2. The obtained first composite oxide particles and lithium carbonate were mixed so that Li / (Ni+Co+Mn)=1.15 to obtain a raw material mixture. The obtained raw material mixture was fired in air at 950°C for 15 hours to obtain a sintered body. The obtained sintered body was crushed, subjected to a dispersion treatment in a resin ball mill for 10 minutes, and then sieved through a dry sieve to obtain a powdered body. From the above, the average particle size 2 D SEM is 0.49 μm, 2 D 10 = 3.0 μm, 2 D 50 = 4.4 μm, 2 D 90 =7.6μm, average particle size 2 D SEM for 2 D 50 Ratio of 2 D 50 / 2 D SEM is 9.0, and the particle size distribution 2 D 90 / 2 D 10 The ratio is 2.5, the Ni disorder amount is 0.9%, and the composition formula is Li 1.15 Ni 0.33 Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles represented by O2 were obtained. The physical properties of the obtained lithium transition metal composite oxide particles are shown in Table 1, and an SEM image is shown in Figure 7.

[0067] [Table 1]

[0068] The lithium transition metal oxide particles produced by the above-mentioned production method are composed of a single particle or a small number of primary particles, so that the lithium transition metal oxide obtained can be efficiently produced without being pulverized to adjust the particle size and then subjected to another heat treatment.

[0069] The lithium transition metal composite oxide particles produced by the above-mentioned production method are as follows: 2 D 50 / 2 D SEM and 2 D 90 / 2 D 10 Since the particle diameter is small, the particles are composed of a single particle or a small number of primary particles, and the particle size is uniform. 2 D SEM is relatively small, 2 D 50 / 2 D SEM is small, 2 D 90 / 2 D 10 Since the Ni content is small and the amount of Ni disorder is small, by using this as the positive electrode active material in a nonaqueous electrolyte secondary battery, a nonaqueous electrolyte secondary battery with excellent output characteristics and durability can be constructed.

Claims

1. 90% particle size of cumulative particle size distribution based on volume 1 D 90 10% particle size 1 D 10 Ratio to 1 D 90 / 1 D 10 preparing composite oxide particles containing nickel, mixing the composite oxide particles and a lithium compound, subjecting the mixture to a heat treatment at a first temperature (first heat treatment), and then subjecting the mixture to a heat treatment at a second temperature higher than the first temperature (second heat treatment) to obtain a first heat-treated product; and dispersing the first heat-treated product, In the first heat treatment, the lithium compound is reacted with the composite oxide particles to reduce the amount of residual lithium compound in a temperature range where the composite oxide particles do not become monoparticles, In the second heat treatment, the residual lithium compound acts as a flux to suppress sintering of particles, thereby growing particles, and The positive electrode active material has an average particle size based on observation with an electron microscope. 2 D SEM 50% particle size of cumulative particle size distribution based on volume 2 D 50 Ratio of 2 D 50 / 2 D SEM The lithium transition metal composite oxide particles have a The composition of the lithium transition metal composite oxide particles is, relative to the total number of moles of metals other than lithium, The ratio of the mole number of nickel is 0.3 or more and less than 0.6, The ratio of the number of moles of cobalt is 0.4 or less, the ratio of the total mole numbers of manganese and aluminum is 0.5 or less; The ratio of the mole number of lithium is 1.0 or more and 1.3 or less, The ratio of the molar numbers of oxygen atoms is 1.9 or more and 2.1 or less.

2. The method according to claim 1, wherein the first temperature is 850°C or more and 950°C or less, and the second temperature is 980°C or more and 1100°C or less.

3. 3. The method according to claim 1, further comprising: mixing the first heat-treated product after the dispersion treatment with a lithium compound to obtain a second mixture; and heat-treating the second mixture to obtain the second heat-treated product.

4. The lithium transition metal composite oxide particles have a particle size of 90% of a cumulative particle size distribution based on volume. 2 D 90 10% particle size 2 D 10 Ratio to 2 D 90 / 2 D 10 The method according to any one of claims 1 to 3, wherein the ratio of the stoichiometric ratio to the total stoichiometric ratio is 4 or less.

5. The composite oxide particles have a particle size of 50% of a cumulative particle size distribution based on volume. 1 D 50 is 1 μm or more and 4 μm or less, The lithium transition metal composite oxide particles have a 50% particle size of a cumulative particle size distribution based on volume. 2 D 50 The method according to any one of claims 1 to 4, wherein the thickness is 1 µm or more and 3 µm or less.

6. The method according to claim 1 , wherein the lithium transition metal composite oxide particles have a ratio of the number of moles of lithium to the total number of moles of metals other than lithium in the composition of the lithium transition metal composite oxide particles of 1.1 or more and 1.2 or less.

7. The above 2 D 50 The above 2 D SEM Ratio to 2 D 50 / 2 D SEM The method according to any one of claims 1 to 6, wherein R is 1 or more and 3 or less.

Citation Information

Patent Citations

  • Lithium transition metal oxide compound for lithium secondary battery positive electrode active material, its manufacturing method and secondary battery using it

    JP2001243949A

  • Lithium composite oxide for nonaqueous electrolyte secondary battery

    JP2008147068A

  • Positive electrode active material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    JP2015038878A